The Moderating Role of Academic Self-Efficacy in the Relationship Between Mobile-Based Cyberloafing and Academic Commitment Among Secondary Students in Babylon, Iraq - Jasem Almahmodi, Safa Nsaif; Golparvar, Mohsen; Abdel-Amir Jassim Al-Ibrahimi, Safaa Abdel Rasoul; Mehdad, Ali (KMAN Counseling & Psychology Nexus, 2024)
Enhancing students’ capacity and ability to make optimal use of available opportunities and resources is of critical importance. This study aimed to investigate the moderating role of academic self-efficacy in the relationship between mobile-based cyberloafing and academic commitment among lower secondary school students in the city of Babylon, Iraq. The research employed a correlational method, and the statistical population consisted of lower secondary school students in Babylon, Iraq, during spring 2024. A total of 368 students were selected through convenience sampling and responded to the Academic Commitment Questionnaire (Huynh, Vogel, & Rabi, 2015), the Mobile-Based Cyberloafing Questionnaire (Askew, 2012), and the Academic Self-Efficacy Questionnaire (McIlroy & Bunting, 2002). Data were analyzed using Pearson correlation coefficients and hierarchical regression analysis via SPSS version 26. The results indicated that mobile-based cyberloafing had a significant relationship with both academic commitment and academic self-efficacy (p < .05). Hierarchical regression analysis further revealed that academic self-efficacy served as a moderating variable in the relationship between mobile-based cyberloafing and academic commitment. Specifically, when academic self-efficacy was high, there was no significant relationship between mobile-based cyberloafing and academic commitment. Based on the findings of this study, it is essential to consider the role of academic self-efficacy in mitigating the negative effects of mobile-based cyberloafing on academic commitment, with the aim of strengthening student capabilities.